Analysis of Organizational Citizenship Behavior (OCB) Variables, Work Stress, Work Communication, Work Climate Affecting Employee Performance and Turnover Intention at PT. Bank Tabungan Negara (Persero) Tbk. Cabang Gresik - Hidayat, Wanda Gema P. A.; Tannady, Hendy (International Journal of Science, Technology & Management, 2023)
This research attempts to illustrate and evaluate "Organizational citizenship behavior's effects (OCB), work stress, work communication, and work atmosphere on employee performance and turnover intention at PT. Bank Tabungan Negara (Persero) Tbk. Cabang Gresik." The research's conclusions are as follows: The OCB of an organization (organizational citizenship behavior) significantly affects performance. Performance is unaffected significantly by work stress. Workplace communication has a big impact on performance. The workplace culture has a tremendous impact on employee performance. Intentions to leave the company are significantly influenced by organizational citizenship behavior (OCB). The likelihood of turnover is significantly impacted by work stress. The intention to turnover is not much impacted by workplace communication. Employee turnover intentions are not much impacted by work environment.